(untitled) (Bangladesh Journal of Botany, 2025)
An incomplete diallel cross design was taken to evaluate the combining ability and application potential of the DH lines. The results revealed significant differences in General Combining Ability (GCA) among the DH lines, with JM104 and JM108 exhibiting high dehydration rates and a strong tendency to form high-yield hybrids. Comprehensive analysis of GCA across agronomic traits indicated that JM104 possesses high combining ability and application value, followed by JM108 and JM105. Superior combinations with high Total Combining Ability (TCA) effects and rapid dehydration rates included JM104×JF004, JM104×PHB1M, and JM108×JF004, which require further multi-year and multi-location trials to fully explore their potential. Genetic parameter analysis suggested that traits such as plant height, ear height, ear length, and kernel rows per ear should be selected in early generations. When configuring hybrids, DH lines with superior traits such as plant height, ear height, ear length, and ear diameter should be selected as parents, with comprehensive consideration of GCA for ear diameter, kernel moisture content, and dehydration rate, as well as Specific Combining Ability (SCA) of the hybrids. Specifically, the enhancement of husk leaf quantity should focus on SCA selection. Bangladesh J. Bot. 54(3): 703-710, 2025 (September) Special